Scene of the Crime [large type] - Dunn, Sharon, 1965- (Love inspired suspense., 2020)
Someone's out to end her life.Can the K-9 unit shield her from harm? Evidence from forensic specialist Darcy Fields could convict a killer - if she survives to testify. A killer seems determined to discredit her, frighten her...and silence her, permanently. Hounded by the press and stalked by a murderer, Darcy must depend on Officer Jackson Davison and his K-9 partner, Smokey, as danger inches nearer and the trial date closes in.